2017
DOI: 10.1007/s10461-017-1847-x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of a Rectal Microbicide Placebo Gel Use in a Preparatory Stage for a Phase I Trial Among Young Men Who Have Sex with Men

Abstract: We examined young gay, bisexual, and other men who have sex with men's (YGBMSM) usage patterns of a pre-coital, applicator-administered rectal placebo gel. An ethnically diverse sample of 94 YGBMSM (aged 18-30 years) were asked to insert hydroxyethylcellulose placebo gel rectally before receptive anal intercourse (RAI) and report their gel use through an interactive voice response system (IVRS) across 12 weeks. We used trajectory analyses to characterize participants' use of the rectal gel over the 12 weeks, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Trajectory analysis is a statistical method to cluster individuals based on temporal changes in an outcome of interest. (Bauermeister et al, 2017) Once participants are classified, researchers then can understand the relationship of adherence behavior of a population to its associated factors. For example, a study of patterns of adherence to antiretroviral therapy (ART) identified behavioral groups associated with improving and worsening adherence over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trajectory analysis is a statistical method to cluster individuals based on temporal changes in an outcome of interest. (Bauermeister et al, 2017) Once participants are classified, researchers then can understand the relationship of adherence behavior of a population to its associated factors. For example, a study of patterns of adherence to antiretroviral therapy (ART) identified behavioral groups associated with improving and worsening adherence over time.…”
Section: Introductionmentioning
confidence: 99%
“…(Corneli et al, 2014) Another study of placebo gel used rectally in the context of receptive anal intercourse (RAI) among men who have sex with men (MSM) and transgender women (TW) found that participants who had more frequent RAI and reported trying a greater number of positions when inserting the gel were more likely to have high adherence across 12 weeks. (Bauermeister et al, 2017) A study examining adherence to a diaphragm as an HIV-prevention method found that older women and those reporting baseline adherence to condoms were more adherent to diaphragm use, while younger women and those with more high-risk behaviors and highrisk partners were less adherent. (van der Straten et al, 2009) However, few studies have applied trajectory analysis to examine adherence patterns in this field, and none have examined rectal microbicide gel use.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the acceptability of potential rectal microbicides is affected by product formulation (i.e., gel, suppository, or douche) [1217], attributed lubrication capacity of gels [18,19], anticipated product effectiveness [17,20,21], application method [19,22,23], packaging and portability of the product [22,24], dosing regimen (i.e., daily, before receptive anal intercourse (RAI), or before and after RAI) [16,17,24], side effects [21,24], type of partner with whom the rectal microbicide will be used [19,24,25], frequency of RAI [26], accessibility of product (i.e., prescription versus over-the-counter) [17,21], ease of use of the product [16], and product’s effect on sexual pleasure [13,15]. However, these findings stem from studies that were either hypothetical (participants expressed their opinions without actually using a product), placebo trials (the products used did not contain agents that could potentially have microbicide properties) or Phase 1 safety trials in small numbers of low-risk participants.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the rectal compartment requires a different product development strategy compared to the vagina [ 5 , 6 ]. Growing evidence in the literature indicates a compelling need to develop safe and effective rectal microbicides (RM) [ 7 , 8 , 9 , 10 ]. Topical administration of products such as gels, douches, fast-dissolving suppositories or inserts containing potent antiretroviral drugs (ARVs) is a promising strategy for on-demand pre- or post-exposure prophylaxis.…”
Section: Introductionmentioning
confidence: 99%